Pengaruh Struktur Modal terhadap Kinerja Keuangan Perusahaan pada Grup Indofood Periode 2020-2024 - Rachmad Dharmawan; Liza Novietta (BADAN PENERBIT STIEPARI PRESS, 2025)
This research was conducted to determine how the capital structure affects the company's financial performance during the period 2020 to 2024. In this case, the capital structure is evaluated through two main indicators, namely the Debt to Equity Ratio (DER) and the Debt to Asset Ratio (DAR). Meanwhile, financial performance is evaluated based on two important measures: Return on Assets (ROA) and Return on Equity (ROE). The approach used in this research is quantitative with a combination of descriptive and verification analysis. The data source comes from the annual financial reports of six Indofood subsidiaries listed on the Indonesia Stock Exchange. To test the relationship between variables, multiple linear regression evaluation is used which is equipped with a classical assumption test to ensure the validity of the model used. From the evaluation results, it was found that the capital structure has a significant impact on financial performance, both when tested as a whole and per indicator. DER shows a positive relationship with ROE, which means that the greater the debt to equity ratio, the higher the potential profit obtained by shareholders. Conversely, DAR turns out to have a negative relationship with ROA. This shows that the greater the proportion of debt to total assets, the company's efficiency in generating profits tends to decrease. The conclusion of this finding highlights the importance of the right capital structure management strategy. Companies need to maintain a balance between the use of debt and equity in order to increase profitability without reducing overall operational efficiency.